ANALISIS KETERSEDIAAN RUANG TERBUKA HIJAU DI PUSAT KOTA KABUPATEN MARA ENIM DENGAN METODE NORMALIZED DIFFERENCE VEGETATION INDEX (NDVI) - Agus, Muhammad; Wijayanti, Ratih; Safitri, Ayu (Universitas Pakuan, 2023)
The development of the city center in various forms can affect Green Open Space (GOS) as a source of oxygen, sports facilities, community recreation facilities, and regional income. This study was conducted at the City Center of Muara Enim Regency. Muara Enim Regency has experienced rapid development in recent years, so it is suspected that there has been a reduction in the area of GOS. This research aims to identify, analyze, and map the provision of GOS in the City Center of Muara Enim Regency. The main data in this research include Landsat 8 satellite image data for 2021-2023. The Normalized Difference Vegetation Index (NDVI) algorithm analysis method is the basis for determining the density of vegetation that makes up the green spaces. Law No. 26 of 2007 on spatial planning states that the proportion of green space in urban areas is at least 30% of the total area. The results showed that the area of dense vegetation in Muara Enim Regency City Center decreased, but the amount of green space in City Center of Muara Enim Regency was 73.57% of the area and still met the proportion of green space set by the government.